2006
DOI: 10.1017/s000305540606237x
|View full text |Cite
|
Sign up to set email alerts
|

Su Casa Es Nuestra Casa: Latino Politics Research and the Development of American Political Science

Abstract: S ince the 1970s, Latino politics research has evolved, alternately responding to real-world political events and demographic changes, embracing new and emerging trends in the broader discipline, and offering new insights of its own that contribute to the development of political science. In so doing, there have emerged both an intellectual foundation and a growing body of empirical results, each of which challenges long-held theories and findings in the discipline more broadly. Thus, Latino politics research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Scholars have noted that Latinos have difficulty establishing a collective group identity due to the disparate and complex nature of their immigration histories (Beltran 2010; Fraga et al 2006). However, the development of linked fate among Latinos as a result of experiences of discrimination and marginalization associated with the rise of anti-immigrant (and anti-Latino) sentiments remains under-studied.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have noted that Latinos have difficulty establishing a collective group identity due to the disparate and complex nature of their immigration histories (Beltran 2010; Fraga et al 2006). However, the development of linked fate among Latinos as a result of experiences of discrimination and marginalization associated with the rise of anti-immigrant (and anti-Latino) sentiments remains under-studied.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, political behavior studies have consistently shown that Latino political engagement lags behind that of Anglos and African Americans across every form of political participation-voting, engagement in protest activity, contacting elected officials, signing petitions, and volunteering (Abrajano & Alvarez, 2010;Fraga et al, 2006;Ramakrishnan & Baldassare, 2004). Political behavior studies looking at other populations have found SES-education, income, and occupation-to be the best predictor of voting.…”
Section: The State Of Latinos In Educationmentioning
confidence: 99%
“…This is true even after taking into consideration Latinos' relative youth, lower SES, and nativity. Scholars argue that feelings of grouplinked fate and the broader social and institutional context also play important roles in explaining Latino political engagement (Fraga et al, 2006;García Bedolla, 2005;Hardy-Fanta, 1993;Ochoa, 2004). Within the realm of education policy, a critical aspect of the institutional context is the electoral rules that govern school board elections, particularly who gets to vote in school board elections.…”
Section: Voting and School Board Representationmentioning
confidence: 99%
“…Thus, Americanization is similar to, but more encompassing than, “incorporation,” which researchers tend to link to assimilation (Gordon, ; Fuchs, ; Bean et al., ; Fraga et al., , ; Abrajano, ) and acculturation (de la Garza, Falcon, and Garcia, ; Hood, Morris, and Shirkey, ; Branton, ; Abrajano, ). Fraga et al.…”
mentioning
confidence: 98%